Cognitive–Behavioral Treatment of Posttraumatic Stress in Patients With Implantable Cardioverter Defibrillators: Results From a Randomized Controlled Trial. Issue 4 (14th July 2016) - Ford, Jessica; Rosman, Lindsey; Wuensch, Karl; Irvine, Jane; Sears, Samuel F.
Abstract: Approximately 20% of patients with implantable cardioverter defibrillators (ICDs) suffer from posttraumatic stress disorder (PTSD) due to a history of cardiac arrest, device implantation, and ICD shock. There has been very little examination of treatment of PTSD symptoms in these patients. This study evaluated the effect of a specific cognitive–behavioral therapy (CBT) intervention for ICD patients with high levels of PTSD symptoms: a manualized program consisting of 8 telephone sessions with a trained counselor, a patient education book, and a stress management procedure on compact disc. Participants were 193 ICD patients, who were randomized to CBT or usual cardiac care (UCC) who completed self‐report surveys at the time of recruitment and 6 and 12 months after initial measurement. Previous publication on the primary research evaluation questions reported that the CBT condition resulted in greater improvement on PTSD and depression symptoms than the UCC for the general population of ICD patients, but did not evaluate the effect on those with elevated symptoms of PTSD. The authors conducted secondary analyses of the effect of treatment on high and low PTSD symptom groups based on a cutoff for the Impact of Event Scale‐Revised (Weiss & Marmar, 1997). Participants in the CBT group who had high symptoms experienced significantly greater symptom reduction from baseline to 12 months ( d = 2.44, p = .021) than the UCC group ( d = 1.12). Participants with low symptoms had small reductions regardless of group assignment ( d = 0.16, p = .031). ICD‐focused CBT was sufficient to produce a large, statistically significant reduction in PTSD symptoms in ICD patients with indications for treatment.